Crystal structure determination from powder diffraction data of the coumarin vanillin chalcone. Issue 4 (13th August 2014) - Ghouili, Afef; Rohlicek, Jan; Ayed, Taïcir Ben; Hassen, Rached Ben
<x content-type="archive" xml:space="preserve">Abstract</x> 4-hydroxy-3-methoxyphenyl-4-hydroxycoumarin chalcone (C19H14O6) was synthesized by the Claisen–Schmidt reaction with the condensation of 3-acetyl-4-hydroxycoumarin with 4-hydroxy-3-methoxybenzaldehyde (vanillin). The new compound was characterized by Fourier transform infrared microscopy, UV–vis 1H, and 13C NMR spectroscopy and its crystal structure was ab initio determined from laboratory X-ray powder diffraction data. The crystal structure is monoclinic with unit-cell parameters a = 14.3181(4), b = 8.040 71(9), c = 13.5524(3), β = 100.3559(13)°, V = 1534.84(6) Å3, and space group P21/c.